Case Report: Anomalous origin of the right coronary artery leading to cardiac arrest induced by sexual activity: a previously unreported pathogenetic condition - Tang, Junchu; Li, Da; Wang, Shuizhu (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe Anomalous Origin of the Right Coronary Artery from the Left Coronary Sinus (ARCA-LCS) is a rare congenital cardiac condition where the right coronary artery emerges from the left sinus instead of the right coronary sinus of Valsalva. The clinical significance of ARCA-LCS lies in its potential to cause myocardial ischemia or sudden cardiac death, particularly under physical exertion. In this case, a patient experienced sudden cardiac arrest during sexual activity, which has not previously been reported.Case presentationSix years ago, a 37-year-old man was admitted with sudden cardiac arrest during sexual intercourse. No previous history of hypertension or diabetes. There was no abnormality in physical examination. Transthoracic echocardiogram, bilateral carotid Doppler ultrasound, and electrocardiogram were normal. Cranial magnetic resonance imaging and magnetic resonance angiography showed no abnormalities. A treadmill exercise test revealed ischemic changes. Coronary computed tomography angiography showed ARCA-LCS, and passage through the vessel wall between the aorta and pulmonary artery.ConclusionThis case illustrates a patient with asymptomatic ARCA-LCS for 37 years who did not receive appropriate treatment during a previous visit, but who subsequently experienced a serious cardiovascular event that demonstrated the potential harm of the disease. Therefore, timely intervention in patients with ARCA-LCS, especially in high-risk groups, is critical to prevent potentially catastrophic cardiovascular events. However, in the present case report, the patient did not experience a similar event during the 6-year follow-up by avoiding overexertion and changing his lifestyle at the time of previous onset of the disease. Further studies are needed to optimize diagnostic and therapeutic strategies for ARCA-LCS.